ANALISIS HUKUM MENGENAI PENJATUHAN SANKSI PIDANA TERHADAP PELAKU USAHA PERTAMBANGAN TANPA TANAH TANPA IZIN USAHA PERTAMBANGAN DI KABUPATEN DELI SERDANG - Zulham Effendy Harahap; Ediwarman Ediwarman; Madiasa Ablisar; Jusmadi Sikumbang Sikumbang (Universitas Sumatera Utara, 2017)
ABSTRACT The definition of mining according of the Law No.4/2009 Article I Paragraph I regarding mineral and coal mining is “part of or all of activity stages in terms of mineral and coal research, management, and business including general investigation, exploration, feasibility study, construction, mining, management, and purification, transportasion and sales, and post mining activities. In the specific law (lex spesialis), particularly, the Law No. 4/2009 regarding mineral and coal mining, the criminal provisions are stipulated in chapter XXIII, Article 158 to article 165. The penal provisions contains in this law regulates various permits such as IUP (Mining Business Permit). IPR, and IUPK. The Ruling of No. 1561/Pid.B/2014/PN.Mdn is about land mining activities. A case on a mining business without a permit happened in marindal, patumbak subdistrict, Deli Serdang District, Sumatera Utara Province. The businessman, in this case, was sendtenced to a year imprisonmen and finet to IDR I Billion based on the article 158 of the Law No.4/2009 regarding mineral and coal mining. The thesis applies judicial normative method with prescriptive analysis. It uses the theory of criminalization. The data of this thesis are legal material including primary, secondary, and tertiary legal materials and non-legal materials. It is also supported by statude, conceptual, and case approaches. The data are analyzed using qualitative method. Based on the research results, it can be concluded that firstly, in Chapter XXIII, Article 158 to Article 165, the provisions regulate various matters regarding IUP, IPR, and IUPK. In the government regulation and regional regulation, the criminal provisions tend to refer to, Law No.4/2009 regarding mineral and coal mining. Secondly, the people of Deli Serdang District Find it difficult to administer the mining permit. Aside from the document administration that takes months, the moral hazard of Deli Serdang District Government, particularly, in mining sector also becomes an abstacle to accelerate the mining permit administration. Theirdly, penal and non-penal provisions are criminal policies whose scopes consist of penal and non-penal. Keywords: Criminal Sancetion, Land Mining, Business Permit